Yiğitbaşı Veli'nin -Tasavvuf- ve -Tarikat- Kavramlarına Bakışı ve Tarikatları Tasnifi - Ögke, Ahmet (Dinî araştırmalar, 2001)
Yiğitbaşı Veli was born in 1505 at Saruhan. in Othoman Period. He is one of the biggest sufis of Turkish Mystic Thought and he is founder of Ahmediyya faction of Khalwetiyya Sufi School. Marmaravi says in his Ahvalü'l-Ebrar caleld booklet practicing moral values is ittisaf and it means Sufısm. Marmaravi says just as İslam is based on five pillars, so Sufism is. Talking little, eating little, sleeping little, withdrawing in to solitude, continious zikr: Each of this pillars are concerned with others. Sufi s actions must not contrary to religious pillars. Sufi must listen to his interior voices. Sufi must interested in his heart s evolution. Sufi paths are divided into two first is right and the second invalid. Marmaravi talks about the sufi paths that are on the sunni path and out of this way in his book Cami u' l-Esrar. Yiğitbaşı Veli, doesn 't accept any kind of sufi that it is opposite religious rules. A sufi way without Kur 'an and Sunnah is impossible. Marmaravis sufi doctrine had a lot of followers in his time and after in Anatolia